THU0464-HPR Nursing evaluation in the etanercept switching from a prefilled syringe into a pen myclic in patients with chronic arthritis. (23rd January 2014) - Garcia-Diaz, S.; Girabent-Farres, M.; Roig, D.; Reina, D.; Cerda, D.; Gonzalez, M.; Figuls, R.; Esteve, J.; Padilla, C.; Corominas, H.
Abstract : Background: Etanercept is an anti-TNF biological therapy, which is available in either a prefilled syringe or a pen myclic. Nursing staff play an important role in the administration and monitoring of this drug. The use of Enanercept in pen form rather than syringe, within our hospital, has prompted this study. Objectives: To evaluate the level of fear prior to the administration, pain post-injection and the level of satisfaction of the patients using prefilled syringe versus pen. To evaluate the usefulness of the training given by nursing staff prior to starting with the pen. To evaluate the preferences of the patients after using both devices: syringe vs pen. Methods: The design of the study was cross-sectional, with patients who have chronic arthritis. The data collection was obtained from questionnaires developed for this purpouse. The study was placed at the Hospital Moises Broggi, Barcelona. All the patients were using prefilled syringe at the beggining of the study and changed into a pen during the study. The first phase (October'11), consisted of a theoretical-practical workshop where the new pen was presented, explained and patients practiced how to used it; a questionnaire was then completed. During the second phase (November-December'11), all patients were given the pen. In January'12, these patients were asked to complete a second questionnaire. Results: 30 patients were included in the study (21 F, 9 M; mean age 51.3±11.54 years). The mean disease duration was 17.17±11.24 years, with a mean of etanercept treatment of 42.67±36.83 months. Of these, 50% had Rheumatoid Arthritis, 27% Psoriatic Arthritis and 20% Ankylosing Spondylitis mainly. Initially, 86.7% of the patients self-injected with the syringe; this increased to 93.3% with the pen. There were no statistically significant differences either with the management of the device between the syringe and the pen (p=0.27), or with the post-injection pain (p=0.5). However, there was a statistically significant increase in the level of fear felt by the patients prior to injecting with the syringe than with the pen (3.75±3.62 Vs 2.35±2.56; p=0.03). Regarding to the current patients' satisfaction, the percentage of patients with a normal or good satisfaction was of 90% with the syringe and 93.3% with the pen. The results indicated that 82.7% of patients found good or very good the education given by nursing staff prior to using the prefilled syringe, compared to 96.7% with the pen (p=0.045); in addition, all the patients referred to the usefulness of the training given by nursing staff prior to using the pen as useful (16.7%) or very useful (83.3%). Finally to mention that 64% of the patients preferred the pen over the prefilled syringe. Conclusions: The means of fear, pain and the difficulty in management of both the syringe and the pen, were low with both devices. The level of fear prior to the administration with the syringe was greater than with the pen. A majority of patients found that the education provided by the nursing staff was good or very good and this was useful or very useful. The pen was the preferred device chosen by the majority of patients. References: Gόmez J et al (2011); Sánchez-Eslava L et al (2011) Paul C et al (2011); Borrás-Blasco J et al (2010) Disclosure of Interest: None Declared